Trans-adapted, reliability, and validity of children fear survey schedule-dental subscale in Bahasa Indonesia - Arlette Suzy; Julian Amriwijaya; Efi Fitriana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: The most frequently used measuring instrument for determination of dental fear in children nowadays is the children’s fear survey schedule-dental scale (CFSS-DS). Purpose: The purpose of this study was to explore the reliability and validity of the scale with Indonesian trans adapted version of the scale, thus the scale can be reliable to be used in other similar research in Indonesia. Methods: Total of 113 participants, who were parent’s 3 to 12 years old children. Children were divided into two age groups, group I 3-6 year old (83 children) and group II 7-12 year old (30 children). Eighty three children from the first group were divided into first dental visit group (30 children) and non first dental visit group (53 children). Test-retest approach was applied to 30 first dental visit children aged 3-6 year old. Original scale was translated to Indonesian language. Result: The result showed the high value of the Cronbach’s coefficient of internal consistency α=0.956. Three factors were extracted by screen test method with Eigen values higher than 1, which explained 93.05% variance of results. Conclusion: CFSS-DS scale is reliable and valid psychometric instrument for dental fear evaluation in children in Bahasa Indonesia. The differences between this study and those of others may appear due to many factors.